Behavioural aspects of business and its role in development of innovations - B. R. Shakirtkhanov (Путеводитель предпринимателя)
Questions of behavioural aspects of business activity are dictated by laws of business and need of its development within civilized norms and rules of the market. However, as well as any open system business is rather susceptible to any negative manifestations of market forces and administrative impact on it from the state and the power.